Effects of cobalt dopant on microstructure and electrical properties of Bi0.5Na0.5TiO3 ceramics - Suwapitcha Buntham (2018)
© 2018, Chiang Mai University. All rights reserved. Co-doped (Bi0.5Na0.5)TiO3 ceramics with varied doping concentration of 0, 0.005, 0.01, 0.02 and 0.03 mol fraction were prepared by conventional solid state reaction method. The firing condition used was 1050 °C for 2 h. X-ray diffraction results showed that all produced ceramics were single phase with a rhombohedral perovskite structure. Due to the replacement of Ti4+ions with Co2+ at B-site, there was a slight shift of X-ray diffraction pattern to the left. SEM micrographs of the ceramics indicated that a small amount of Co addition could eliminate pores and improved densification. However, above 0.01 Co mol fraction, excessive grain growth occurred and large pores were again observed. The dielectric constant and piezoelectric coefficient reached maximum values of 670 and 105 pC/N, respectively, in the sample doped with 0.01 Co mol fraction. Ferroelectric characteristics were also found to increase with increasing dopant concentration.